Detection of Leptospira species targeting 16S rRNA, rpoB, and lipL32 gene from clinical and environmental sources - Zulkifli, Nurul Farhana (2019)
Leptospirosis is currently emerging globally as reflected by the increase in the number of Leptospira infections. The scope of research on identification of individual Leptospira species through a rapid assay in local setting is still lacking. This study attempts to determine the Leptospira species distribution in clinical and environmental samples using molecular approach. The blood for clinical samples (n=64) were collected from patients whom have been suspected with leptospirosis, and the environmental samples (n=105) consisting of soils and waters were collected from areas with potential sources of Leptospira transmission. All samples were directly extracted for DNA and subjected to PCR using three sets of established primers; 16S rRNA, rpoB, and lipL32. Positive samples were further analysed on their DNA sequences and also through phylogenetic analysis. Six clinical samples were amplified for 16S rRNA gene and four clinical samples showed an amplification of rpoB gene that was highly matched to pathogenic Leptospira spp. in GenBank. Out of 13 positive results amplified for 16S rRNA from environmental samples, only five were detected to have been contaminated by Leptospira spp. while the others showed a higher number of contamination by different species of bacteria. The BLAST similarity results for clinical samples targeting lipL32 showed that only one out of 64 samples was highly matched to pathogenic Leptospira spp. in GenBank. The phylogenetic trees constructed shows that the positive clinical samples were clustered into group with pathogenic Leptospira spp. while the environmental samples showed a clustering into uncultured Leptospira. Overall, this study showed the ability of the molecular approach in combination with PCR in determine Leptospira species directly on both clinical and environmental samples. Although the number of positive samples were low, but the tendency of the species to appear in limited positive samples may infer the species as the likely agents in causing leptospirosis at this study setting.